A COMPREHENSIVE ACCOUNT ON THE INSECT DIVERSITY POTRAYED IN THE HOLY QUR'AN - Riyaz, Muzafar (Journal of Islam and Science, 2021)
Insects are one of the most fascinating groups of organisms that evolved some 300 million years back in the Devonian period. With the remarkable body structure, shape, and flight adaptability, Insects have outnumbered every other organism and become the dominant group of organism's earth has ever witnessed. Insects deliver a number of ecosystem services like pollination of flowering crops, as decomposers, vectors, pests, predators, etc. Since insects play an important role in human life; a number of Insects have been mentioned several times in the holy Quran. The present study is a review of the insects that have been described in the Quran. In the present era of large-scale industrialization, urbanization and many other factors like climate change, global warming, pesticide pollution; insect diversity is under a very serious threat and many species are on the verge of extinction and a number of species are threatened and vulnerable including some species of bees. Management and conservation of these precious species are need of the hour and cutting-edge strategies can save these insects from further decline.